Soil Environments Influence Gut Prokaryotic Communities in the Larvae of the Invasive Japanese Beetle Popillia japonica Newman - Avila-Arias, Helena; Scharf, Michael E.; Turco, Ronald F.; Richmond, Douglas S. (Frontiers in Microbiology, 2022)
Invasive scarab beetles, like the Japanese beetle Popillia japonica Newman (JB), spend most of their lives as larvae feeding in the soil matrix. Despite the potential importance of the larval gut microbial community in driving the behavior, physiology, and nutritional ecology of this invasive insect, the role of soil biological and physicochemical characteristics in shaping this community are relatively unknown. Our objectives were to (1) characterize the degree to which larval gut microbial communities are environmentally acquired, (2) examine the combined effects of the gut region (i.e., midgut, hindgut) and local soil environments on gut microbial communities, and (3) search for soil physicochemical correlates that could be useful in future studies aimed at characterizing gut microbial community variation in soil-dwelling scarabs. Gut communities from neonates that were never in contact with the soil were different from gut communities of third instar larvae collected from the field, with neonate gut communities being significantly less rich and diverse. The influence of compartment (soil, midgut, or hindgut) on prokaryotic α- and β-diversity varied with location, suggesting that JB larval gut communities are at least partially shaped by the local environment even though the influence of compartment was more pronounced. Midgut microbiota contained transient communities that varied with the surrounding soil environment whereas hindgut microbiota was more conserved. Prokaryotic communities in the hindgut clustered separately from those of soil and midgut, which displayed greater interspersion in ordination space. Soil cation exchange capacity, organic matter, water holding capacity, and texture were moderately correlated (≥29%) with gut prokaryotic microbial composition, especially within the midgut. Findings suggest that microbial communities associated with the JB gut are partially a function of adaptation to local soil environments. However, conditions within each gut compartment appear to shape those communities in transit through the alimentary canal.